Stress characteristics of a laminated architectural glazing subjected to blast loading - Wei, Jun; Shetty, Mahesh S.; Dharani, Lokeswarappa R. (Computers & structures, 2006)
The dynamic response of a rectangular laminated architectural glazing subjected to blast loading from a bomb explosion on ground is studied. For the sake of computational efficiency, blast loading parameters are formulated using tabular data available in the literature. In the analysis, the glass plies are modeled as linear elastic, while the polymer interlayer is treated as viscoelastic. The results show that the bulk modulus of the interlayer has no effect on the dynamic response of the laminated panel. However, the short-time shear modulus significantly affects the behavior of the panel. Through-the-thickness distribution for stresses and displacements is nearly linear for short-time shear modulus of the interlayer.